2007
DOI: 10.1038/sj.ijo.0803551
|View full text |Cite
|
Sign up to set email alerts
|

Dietary energy density increases during early childhood irrespective of familial predisposition to obesity: results from a prospective cohort study

Abstract: Objective: This study compared 4-year changes in daily energy density (ED; kcal/g) in children born at different risk for obesity, characterized the stability of ED and examined associations between ED and child body composition. Design: Prospective cohort study to measure habitual dietary ED of children who are born at different risk for obesity. Subjects: Children who were born at high risk (n ¼ 22) or low risk (n ¼ 27) for obesity based on maternal pre-pregnancy weight. Measurements: Three-day food records … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 35 publications
1
32
2
1
Order By: Relevance
“…Recently, it was shown that the ED of the self-selected diet of children increased over time without differences between children born at different risks for obesity, reached its peak during adolescence (50) and then declined during adulthood. This finding suggests that dietary ED may be a dietary trait more environmentally than genetically influenced (51).…”
Section: Energy Densitymentioning
confidence: 85%
“…Recently, it was shown that the ED of the self-selected diet of children increased over time without differences between children born at different risks for obesity, reached its peak during adolescence (50) and then declined during adulthood. This finding suggests that dietary ED may be a dietary trait more environmentally than genetically influenced (51).…”
Section: Energy Densitymentioning
confidence: 85%
“…These data are displayed for descriptive purposes only. A detailed discussion of these results can be found in a previously published paper by Kral et al (37) that investigated the changes in dietary energy density in children in this cohort over time. Relation between daily food intake and energy density and between daily energy intake and energy density…”
Section: Daily Food Intake Energy Intake and Energy Densitymentioning
confidence: 94%
“…All dietary outcome measures were averaged across the total number of days of completed records included in the analyses. A detailed description of the children's daily energy density and daily energy intake is provided elsewhere (37).…”
Section: Dietary Outcome Measuresmentioning
confidence: 99%
“…In accordance, the WHO recommends reducing dietary energy density and increasing fiber intake in order to prevent and treat overweight [2]. However, so far only few studies [3][4][5][6][7] have examined the association between energy density and weight gain, and only a few of them have investigated children and adolescents in a prospective study design [6][7][8]. Short-term studies demonstrate that energy density influences energy intake [4,[9][10][11], but longterm effects of energy density and health outcomes are largely unexamined.…”
Section: Introductionmentioning
confidence: 99%